The Function of Markum Discourse in Learning Islamic Tasawuf in the Sasak Community - Aswandikari S; I Nyoman Weda Kesuma; I Nyoman Suarka; Ida Bagus Rai Putra (Budapest International Research and Critics University, 2022)
This paper was written based on the results of qualitative research which aims to examine some of the functions of Markum's discourse in learning Islamic Sufism in the Sasak community of Lombok. This study uses Bragenski's theory with the focus of its study on text studies. The Sasak people of Lombok view that the Markum manuscript is a very acceptable discourse. This is because this manuscript has functions, including: 1). The function of Markum's discourse is to grow a sense of beauty, 2). Markum's function which positions Mursyid as an Important Figure, 3). Markum Functions that Form good Adab, especially when studying, and 4). Markum's function that makes Murshid a source of knowledge. With the facts above, it can be said that the Markum discourse has a very significant function in learning Sasak Islamic Sufism. In other words, Sufism learning through Markum's discourse can shape the character of a civilized society starting or commendable. This is what makes the Sasak people very synonymous with the character of Islam.